1994
DOI: 10.1093/infdis/170.3.701
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Epidemic Strain 0139 Is Closely Related To The Pandemic Strain 01 Of Vibrio Cholerae [X]

Abstract: A new Vibrio cholerae serogroup O139 strain of unknown origin recently emerged in India and Bangladesh, causing a major outbreak of cholera. The genetic relationship between this epidemic strain and the O1 strain responsible for the 7th pandemic of cholera was studied by analyzing the DNA polymorphism of V. cholerae by pulsed-field gel electrophoresis and arbitrarily primed polymerase chain reaction. The restriction patterns of the reference strain O139 Bengal and 10 wild O139 strains isolated early in the Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
41
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 12 publications
2
41
0
1
Order By: Relevance
“…It has been proposed that serogroup O139 originated from an El Tor strain that obtained the O139 antigen biosynthesis and some other gene clusters (4,52,55). However, some portion of VPI-II is absent from all of the test toxigenic O139 strains isolated through the past years, and an additional five common missing genes in the superintegron in the toxigenic O139 strains have been documented (in comparison with all toxigenic El Tor strains).…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that serogroup O139 originated from an El Tor strain that obtained the O139 antigen biosynthesis and some other gene clusters (4,52,55). However, some portion of VPI-II is absent from all of the test toxigenic O139 strains isolated through the past years, and an additional five common missing genes in the superintegron in the toxigenic O139 strains have been documented (in comparison with all toxigenic El Tor strains).…”
Section: Discussionmentioning
confidence: 99%
“…However, the O139 serogroup is still present on the Indian subcontinent and, in some areas, is the predominant cause of cholera (23). Interestingly, several studies have proposed that the origin of the serogroup O139 strain was an El Tor strain that obtained the O139 biosynthesis genes (as well as the SXT element and a capsule) via antigenic switching from a donor strain (3,44,60,65). Recently, it has been proposed based on comparative sequence analysis that an O22 serogroup maybe a possible donor for the O139 serogroup (17,67).…”
mentioning
confidence: 99%
“…Recent studies have indicated that the ctxAB and tcpA genes may also be present in "nonepidemic" (i.e., other than O1 and O139) V. cholerae serogroups (7,8,9,18,23,24,26). While the genetic relatedness of O1 and O139 isolates has been well documented (1,2,3,12), we know less about the genetic relatedness and phylogeny of ctxAB-and tcpA-positive isolates in other serogroups, and such data are critical for understanding why and how pandemic-causing V. cholerae strains emerge.…”
mentioning
confidence: 99%